The Indus Basin is indispensable: An agro- hydropower dependency of India and Pakistan - Dr. Shaista Tabassum (Journal of Political Studies, 2018)
The importance of water is undeniable for the human and states’ survival. Since World water level is constantly on decline, the future conflicts are most likely to develop over the control of this dying source of life. South Asian region is one of the vulnerable region of the World due to the nuclear neighbors; India and Pakistan. There are many unresolved issues including distribution and sharing of the waters of Indus Basin comprises of six rivers; the Indus, Jehlum, Chenab, Ravi, Beas and Sutlej. Both these states have heavy reliance on the water of these rivers, since Pakistan is an agriculture state at the same time almost 60% of Indian society lives in rural areas and agriculture production in India has significant contribution in the total GDP of the state. Moreover, the hydropower generation in both these states is also attached to the uninterrupted flow of the water from the rivers. Thus the water of the Indus basin is indispensable reality of the South Asian politics and tussle for the control over it may lead to future conflict between the two states.